A method of synthesizing generalized Gaussian noise based on spline approximants. Issue 7 (1st October 2018) - El Hilali, A.; Monir, A.; Mraoui, H.
Abstract: A method of synthesizing generalized Gaussian noise processes based on spline approximation is presented. We formulate an algorithm that computes a sequence of convergent spline approximants to approximate the inverse of the regularized incomplete gamma function which arises in the inverse distribution function of generalized Gaussian noise. The results of numerical simulations are presented and compared from the point of view of accuracy.